Corporate Governance and Internet Financial Reporting: Evidence from Public Companies in Indonesia - Tumewu, James; Ardini, Lilis; Rachmawati, Rani (Indonesia Academia Research Society, 2024)
Internet financial reporting provides the fastest information about company conditions, including financial and business data. This study examines the impact of corporate governance mechanisms on Internet Financial Reporting. Purposive sampling was used to select the sample, which included 105 companies in 2022. Linear regression analysis was employed to analyze the data. The study findings indicate that the audit committee and audit firm influence Internet Financial Reporting. At the same time, the educational background of the board of directors, board of commissioners, and ownership concentration have no significant effect. The increasing adoption of technology in financial reporting has led to internet-based financial reporting, enabling companies to present their financial statements on time and facilitate the dissemination necessary information regarding investment potential and opportunities before the data becomes obsolete. This study investigates the role of corporate governance mechanisms in influencing the timeliness of Internet Financial Reporting. The timely dissemination of financial information through internet-based reporting is crucial for investors to make informed decisions, allowing them to access relevant data before it becomes outdated. This study provides insights into the specific corporate governance factors that can impact the timeliness of this reporting, which is an important consideration for companies seeking to improve their transparency and disclosure practices.